Minimum Wage Non-Compliance: Evidence from Ireland - Seamus McGuinness; Paul Redmond; Judith Delaney (Institute of Labor Economics (IZA), 2020)
We use a unique question from the Irish Labour Force Survey that captures the reasons for workers being paid below the minimum wage. Compared to existing work, this allows us to more precisely identify sub-minimum wage workers. We find that 5.6 percent of minimum wage workers are paid below the minimum wage for reasons other than those permitted under legislation. This is considerably lower than estimates reported in the existing literature.
Keywords: J22; J23; J31; J32; 330; non-compliance; minimum wage